Method for treating mechanical pulp with biological enzyme extracted from pure plants and paper product prepared from treated mechanical pulp

By using peroxidase and H2O2 bleaching technology extracted from pure plant, the problem of lignin removal and environmental pollution on the surface of the mechanical pulp is solved, and the fiber strength and whiteness are improved and environmental safety is enhanced.

CN119686147AActive Publication Date: 2025-03-25SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311238172.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The prior art has problems of large amounts, difficulty in recycling and environmental pollution when removing lignin on the surface of mechanical pulp, and has limited effect on improving fiber strength and whiteness.

Method used

The mechanical pulp of cizhu, reed and eucalyptus were treated with peroxidase extracted from pure plants. Combined with H2O2 bleaching technology, the enzyme dosage, treatment time and H2O2 addition amount were optimized to improve fiber strength and whiteness.

Benefits of technology

The fiber strength and whiteness of the mechanical slurry are significantly improved, the total content and surface content of lignin are reduced, the pollution to the environment is reduced, and the natural enzymes are used to reduce the application of chemical reagents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686147A_ABST
    Figure CN119686147A_ABST
Patent Text Reader

Abstract

The invention provides a method for applying biological enzyme extracted from pure plants to papermaking pulp treatment, and particularly relates to applying peroxidase extracted from pure plants to delignification treatment before H2O2 bleaching of mechanical pulp of neosinocalamus affinis, reed and eucalyptus, core parameters such as enzyme dosage, enzyme treatment time and H2O2 adding amount in the treatment process are optimized, and the content of the biological enzyme extracted from the pure plants is improved. The total lignin content, the surface lignin content and the fiber form of a treated sample are measured, an optimal treatment scheme is determined, and compared with other conventional enzyme treatment methods, the optimal treatment scheme is more beneficial to improving the fiber strength and whiteness of treated pulp; molecular docking simulation is carried out on a model of peroxidase extracted from a pure plant and lignin model substances (LMC) with different polymerization degrees, so that information of interaction between the peroxidase and the LMC is obtained, and an action mechanism of the peroxidase and the lignin is obtained; and reliable evidence support and technical reference are provided for extracting peroxidase from pure plants to remove lignin on the surface of the mechanical pulp and promoting the feasibility of subsequent H2O2 bleaching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lignin removal from papermaking mechanical pulp, and in particular to a method for treating mechanical pulp with a biological enzyme extracted from pure plants and a paper product prepared from the treated mechanical pulp. Background Art

[0002] Removing lignin from the surface of pulp is an important way to modify and improve the quality of mechanical pulp. In 2021, Professor Schuur's team in Sweden proposed that "removing lignin from low-energy mechanical pulp under mild conditions by deep eutectic solvents (DES) can be used as a green alternative to traditional delignified fiber (chemical pulp) for papermaking". They tested DES composed of lactic acid and choline chloride to gently cook Norway spruce mechanical pulp at 100-130°C. The final lignin content dropped to 14%, the delignified pulp yield was about 50%, and the fiber length was 0.6mm. Schuur's research points out an important direction for the development of mechanical pulp technology, but the chemical reagents they use still have problems such as large dosage, difficult recycling and potential pollution to the environment. In addition, scholars believe that, unlike chemical pulping, for the purpose of mechanical pulp modification, simply removing the surface lignin is sufficient to improve the hydrophilicity and bonding strength of the fiber surface. The combined removal of surface lignin from mechanical pulp by enzyme treatment and hydrogen peroxide bleaching is a more practical solution than mild cooking with DES.

[0003] In the research on gentle removal of lignin, the Nanjing Forestry Institute of the Chinese Academy of Forestry carried out such research in 2000. They treated wheat straw chemical pulp with xylanase (X) and then bleached it with H2O2 (P). The whiteness increased by 9% ISO. The XP1P2 bleaching sequence was used to finally obtain a pulp whiteness of 60% ISO. Chandra et al. treated fir TMP with laccase and then bleached it with H2O2. The laccase treatment can increase the final whiteness by 1.5-2.5% ISO and reduce the H2O2 consumption by 15-20%. Qiu Wenxiu of Qilu University of Technology treated hardwood APMP pulp with laccase / 1-hydroxybenzotriazole (HBT) system. When the enzyme dosage was 2U / g, the whiteness increased from 56.3% ISO to 57.6% ISO, the tensile strength increased from 23.0N·m / g to 24.9N·m / g, and the tear index increased from 2.8mN·m 2 / g increased to 3.4mN·m 2 / g. Peroxidase also has the function of directly removing lignin from mechanical pulp, but there are few research reports on the direct removal of lignin from the surface of mechanical pulp by peroxidase, as well as the promotion of H2O2 bleaching and the improvement of fiber strength. In particular, how to apply natural plant peroxidase extracted from plants to the removal of lignin from mechanical pulp for papermaking, the exploration and determination of the lignin removal mechanism and the optimization of process conditions, so as to improve the removal efficiency and quality of lignin from mechanical pulp for papermaking, to improve the strength and whiteness of pulp fibers, and then to improve the whiteness and strength of paper obtained after mechanical pulp sheeting. At the same time, the use of natural enzyme treatment can reduce the use of other chlorine-containing chemical reagents in the lignin removal process for papermaking to improve environmental safety and reduce environmental pollution, which is of great significance and application prospects to those skilled in the art. Summary of the invention

[0004] In order to solve the above-mentioned problems, the present application provides a method for applying a pure plant-extracted biological enzyme to papermaking pulp delignification, specifically, applying a pure plant-extracted peroxidase to pulp for three different types of paper products, specifically, delignification treatment of bamboo, reed and eucalyptus mechanical pulp before H2O2 bleaching, and optimizing various core parameters in the treatment process, such as enzyme dosage, enzyme treatment time and H2O2 addition amount, and determining the total lignin and surface lignin content and fiber morphology of the treated samples to determine the optimal treatment scheme. Compared with the conventional treatment methods of other enzymes, the optimal treatment scheme greatly improves the fiber strength and whiteness of the treated pulp; in addition, the inventors also used a model of pure plant-extracted peroxidase to perform molecular docking simulation with lignin model substances (LMC) with different degrees of polymerization to obtain information on the interaction between the enzyme and LMC, which is used to deeply understand the mechanism of action of peroxidase and lignin, and provides reliable evidence support and technical reference for the feasibility of pure plant-extracted peroxidase to remove surface lignin from mechanical pulp and promote subsequent H2O2 bleaching.

[0005] The specific technical solutions adopted in this application are as follows:

[0006] A method for treating mechanical pulp using biological enzymes extracted from pure plants, specifically comprising: the treatment method is completed according to any of the following treatment processes:

[0007] Treatment process (A): using natural peroxidase to treat mechanical pulp at pH 5.0 and temperature 60°C for 2-6 hours, the amount of peroxidase added is 0.5-1.5 g / kg of absolute dry pulp, the reaction concentration of the mechanical pulp is 10%, and the mechanical pulp is washed with deionized water to balance the moisture to complete the treatment;

[0008] Treatment process (B): firstly, the mechanical pulp is treated with natural peroxidase at pH 5.0 and temperature 60°C for 2-6 hours, the peroxidase addition amount is 0.5-1.5 g / kg absolute dry pulp, 5 g / L EDTA is added to the mechanical pulp treated with peroxidase, the mechanical pulp to be treated with EDTA is placed in a polyethylene sealed bag, kneaded to mix the mechanical pulp and the liquid medicine evenly, and placed in a 60°C constant temperature water bath for 60 minutes, cooled to room temperature after the end, and washed with deionized water to adjust the solid content to 10%; the mechanical pulp treated with EDTA is bleached with H2O2, and the process conditions are H2O2 addition of 40 g / L, NaOH 20g / L, MgSO45g / L, mechanical pulp concentration 10%, react at 80°C for 120min; during the reaction, rub once every 15min to ensure uniform reaction, wash with deionized water to neutral after bleaching, balance the moisture, and complete the treatment. As a further improvement to the above scheme, the peroxidase is extracted from the leaves of Eryngium serrata, and the enzyme activity of the peroxidase is 35.64±4.77U / mL.

[0009] As a further improvement to the above scheme, when the mechanical pulp is bamboo mechanical pulp, the enzyme dosage of the peroxidase in the peroxidase treatment process is 1.5 g / kg 绝干浆 , treatment time 4h, H2O2 addition amount in H2O2 bleaching process 0.3g / L; when mechanical pulp is reed mechanical pulp, the enzyme dosage of peroxidase in peroxidase treatment process is 1.5g / kg 绝干浆 , treatment time 6h, H2O2 addition amount in H2O2 bleaching process 0.3g / L; when mechanical pulp is eucalyptus mechanical pulp, the enzyme dosage of peroxidase in peroxidase treatment process is 1.5g / kg 绝干浆 , treatment time is 4h, and the amount of H2O2 added during H2O2 bleaching is 0.3g / L.

[0010] As a further improvement to the above scheme, when the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the acid-soluble lignin of the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated according to treatment process (B) is reduced by 34.8%, 19.0%, and 26.8%, respectively, and / or the Kl ason lignin is reduced by 13.4%, 15.9%, and 21.4%, respectively, and / or the total lignin is reduced by 14.8%, 12.5%, and 17.9%, respectively.

[0011] As a further improvement to the above scheme, when the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the acid-soluble lignin of the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated according to treatment process (A) is reduced by 8.7%, 4.8%, and 7.3%, respectively, and / or the Klason lignin is reduced by 1.6%, 2.3%, and 5.5%, respectively, and / or the total lignin is reduced by 3.7%, 4.2%, and 3.6%, respectively.

[0012] As a further improvement to the above scheme, when the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the content of C atoms connected only to saturated C atoms or hydrogen atoms in the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated by process (A) is reduced by 3.1%, 1.9%, and 11.4%, respectively, and the content of C atoms connected to one carbonyl O atom or two non-carbonyl O atoms is increased by 8.8%, 11.41%, and 3.8%, respectively.

[0013] As a further improvement to the above scheme, when the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the content of C atoms connected only to saturated C atoms or hydrogen atoms in the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated by process (B) is reduced by 16.8%, 20.4%, and 39.4%, respectively, and the content of C atoms connected to one non-carbonyl O atom is increased by 15.8%, 17.7%, and 37.3%, respectively.

[0014] As a further improvement to the above scheme, specifically, when the mechanical pulp is reed mechanical pulp, after being treated by treatment process (A), the O / C is increased by 1.61% compared with the original pulp; after the reed mechanical pulp is treated by section X, the O / C is increased by 1.61% compared with the original pulp, and the surface lignin concentration is reduced by 3.22%; when the mechanical pulp is bamboo mechanical pulp, after being treated by treatment process (A), the O / C of bamboo mechanical pulp is increased by 1.36% compared with the original pulp, and the surface lignin concentration is reduced by 2.72%; when the mechanical pulp is eucalyptus mechanical pulp, after being treated by treatment process (A), the O / C of eucalyptus mechanical pulp is increased by 1.24%, and the surface lignin concentration is reduced by 2.48%.

[0015] As a further improvement to the above scheme, when the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the fiber lengths of the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated by process (B) are reduced by 9.2%, 7.6%, and 6.7%, respectively.

[0016] The present application also provides a paper product prepared by treating mechanical pulp using the above-mentioned method of treating mechanical pulp with a biological enzyme extracted from pure plants, wherein the paper product satisfies at least one of the following conditions (1) to (5):

[0017] (1) The whiteness of the bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp paper products obtained by the treatment process (A) are 40.70% ISO, 40.1% ISO and 40.61% ISO respectively;

[0018] (2) The paper products made of bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by treatment process (A) have whiteness increased by 3.68% ISO, 3.35% ISO and 5.51% ISO respectively compared with the paper products made of the original pulp;

[0019] (3) The paper products prepared from the bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by the treatment process (B) have tensile indices of 8.57 N·m / g, 5.60 N·m / g and 25.69 N·m / g, respectively;

[0020] (4) The tensile index of the paper products prepared from the bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by the treatment process (B) is increased by 50.7%, 61.1% and 22.3% respectively compared with the tensile index of the original pulp;

[0021] (5) The tearing index of paper products made from bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by treatment process (B) was increased by 53.2%, 36.2% and 11.0% compared with the paper products made from original pulp, and the bursting index was increased by 2.4%, 10.2% and 7.3%, respectively.

[0022] Beneficial technical effects

[0023] The present invention takes bamboo, reed and eucalyptus mechanical pulp as the object, studies the delignification process of peroxidase PRLP (peroxidase, extracted from soft-leafed thorny palm leaves, recorded as PRLP, in order to reduce redundancy, the subsequent specification uses PRLP to abbreviate the natural extracted peroxidase used in this application) treatment (X section), EDTA chelation treatment (Q section) and H2O2 bleaching treatment (P section), analyzes the change of lignin concentration and the influence of XQP treatment on the physical properties and fiber morphology of pulp, including:

[0024] Peroxidase, as a natural plant extract enzyme for pretreatment of three mechanical pulps, can improve whiteness and enhance mechanical strength. By exploring and optimizing the enzyme dosage, treatment time and the amount of H2O2 cofactor added, the optimal enzyme treatment scheme for X-section bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp was obtained, and the enzyme dosage was 1.5g / kg. 绝干浆, the treatment time was 4h, 6h and 4h respectively, and the amount of H2O2 added was 0.3g / L. After XQP treatment, the whiteness of bamboo pulp, reed pulp and eucalyptus pulp increased by 11.67%ISO, 15.06%ISO and 18.03%ISO respectively, and finally reached 48.69%ISO, 51.81%ISO and 53.13%ISO. XQP treatment increased the tensile index of bamboo pulp, reed pulp and wood pulp by 59.3%, 66.2% and 22.3% respectively, and the tear index by 53.2%, 36.2% and 11.0% respectively, and the effect was better than that of peroxidase extracted from other plants.

[0025] After treatment with PRLP peroxidase, the lignin of bamboo pulp, reed pulp and eucalyptus pulp was significantly removed. Compared with the original pulp (pulp without any treatment), the total lignin decreased by 3.7%, 4.2% and 3.6% respectively; the surface lignin content decreased by 2.72%, 3.22% and 2.48% respectively. PRLP peroxidase not only removes the lignin on the surface of pulp fiber, but also has a significant auxiliary gain effect on the subsequent H2O2 bleaching to remove lignin. Specifically, the total lignin of bamboo pulp, reed pulp and wood pulp decreased by 14.8%, 12.5% ​​and 17.9% respectively, and the surface lignin decreased by 25.72%, 28.92% and 36.80% respectively after XQP treatment. After peroxidase and subsequent H2O2 treatment, the fiber morphology of the three mechanical pulps did not change significantly, but the microscopic morphology reflected that the hydrophobic particles on the fiber surface were reduced and more hydrophilic microfibrils were exposed. Further molecular docking showed that lignin monomers, dimers, trimers, tetramers and pentamers can enter or approach the peroxide active area and form a stable bond with the PRLP enzyme. The size and structure of these structural groups determine their binding energy at the effective site. The molecular volume of the lignin model is roughly linearly related to the binding energy. The larger the molecular volume, the smaller the absolute value of the binding energy. From the perspective of computer simulation, it is proved that PRLP can interact with lignin. This has laid a broad technical theoretical and data support for the application of naturally extracted biological enzymes, especially peroxidases, in mechanical pulping to remove lignin, and has further expanded the simplified, efficient and extensive application of naturally extracted biological enzymes in removing lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : Mechanical pulp XPS full spectrum and C1s peak decomposition spectrum;

[0027] Figure 2 : Microscope image of mechanical pulp fiber treated with XQP;

[0028] Figure 3 : AFM images of mechanical pulp before and after XQP treatment;

[0029] Figure 4: Relationship between the docking binding energy and molecular volume of PRLP and lignin model. DETAILED DESCRIPTION

[0030] The technical solutions of the specific embodiments of the present invention will be clearly and completely described below in combination with various specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods described in the following embodiments are all conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained through ordinary commercial channels.

[0031] Description of experimental reagents

[0032] Ethylenediaminetetraacetic acid (analytical grade) was purchased from Aladdin Reagent Company; magnesium sulfate (analytical grade) was purchased from Sinopharm Chemical Reagent Company; other reagents were of analytical grade.

[0033] The raw material acquisition method and related testing methods of this application include:

[0034] The natural biological enzyme used in the present application is a peroxidase, which is extracted from the leaves of Eryngium serrata, denoted as PRLP. The extraction method includes:

[0035] A. Obtaining crude peroxidase solution

[0036] The natural plant is collected to extract peroxidase, and the process includes:

[0037] Wash with deionized water and drain; weigh 100g of leaves, cut the leaves to less than 2cm, mix with 150mL of phosphate buffer solution with a concentration of 0.01mol / L and pH 5, put into a plant wall breaking machine for high-speed wall breaking for 1min to obtain a homogenate, then filter with 8 layers of absorbent cotton gauze, and then centrifuge for 10min to remove the filter residue to obtain a clear liquid, which is used as the initial liquid for subsequent separation and extraction, recorded as water extract; slowly drip the water extract into a certain volume of acetone, stirring while dripping, let it stand at 4℃ for 15min, centrifuge for 8-11min to remove the supernatant, obtain a precipitate, dissolve the precipitate with phosphate buffer, make the volume to 100mL, centrifuge again to remove insoluble matter, and obtain a crude enzyme solution;

[0038] B. Purification of crude peroxidase solution

[0039] The crude enzyme solution obtained by acetone extraction is pumped into an ion exchange chromatography column to remove pigments and impurities, specifically including:

[0040] (1) Ion exchanger pretreatment: DEAE cellulose-DE52 was soaked in deionized water for 3 h, soaked in 0.5 mol / L NaOH solution for 30 min, then washed with deionized water until neutral, and then soaked in 0.5 mol / L HCl solution for 30 min and washed again until neutral;

[0041] (2) Column loading: The pretreated DEAE cellulose-DE52 is loaded into the chromatography column, and the chromatography column is fully equilibrated with a 0.01 mol / L phosphate buffer solution with a pH of 5;

[0042] (3) Sample loading: 7 mL of crude enzyme solution was added and balanced with 15 mL of phosphate buffer solution;

[0043] (4) Elution and collection: During elution, 2 mol / L NaCl solution and phosphate buffer solution were used for gradient mixed elution. One tube of sample was collected every 5 minutes. The elution time was 2 hours, and a total of 24 tubes of samples were collected. The peroxidase activity of each tube of sample was detected.

[0044] (5) Regeneration of the exchanger: Use 1 mol / L HCl and 1 mol / L NaOH for transformation regeneration. If the regenerated ion exchanger is not used for a long time, store it at 4°C to prevent microbial growth;

[0045] C. Desalting and freeze drying of peroxidase

[0046] The enzyme solution after ion exchange chromatography is desalted with an ultrafiltration centrifuge tube, the enzyme solution is loaded into the ultrafiltration centrifuge tube, centrifuged at 5000rpm for 8-11 minutes, the enzyme trapped in the centrifuge tube is dissolved with deionized water, centrifuged again, and the above operation is repeated many times until Cl- is not detected in the centrifuge liquid passing through the filter membrane; finally, the trapped enzyme is dissolved in phosphate buffer, and freeze-dried into powder with a vacuum freeze dryer to obtain peroxidase.

[0047] Wherein, in step A, the centrifugation condition is 4°C and the rotation speed is 9000-12000rpm; in step B, the diameter of the chromatography column is 1.3-1.7cm and the length is 30cm.

[0048] After extraction, the obtained natural catalase activity was measured to be 35.64±4.77U / mL, the best reaction pH was pH 5.0, and the temperature was 60°C.

[0049] The mechanical pulp raw materials used in this application are laboratory-made reed, bamboo and eucalyptus mechanical pulp (in order to reduce redundancy, bamboo pulp, reed pulp and wood pulp are used as abbreviations in the following records respectively), and the preparation process is as follows:

[0050] Cut the reed stalks into 3-5cm long pieces, cut the bamboo slices and eucalyptus slices into 0.5cm×2cm pieces, and soak them in deionized water for 12 hours. Put the soaked reed stalks and bamboo slices directly into a high-consistency disc mill (2500-Ⅱ, Japan KRK Company) for pulping, and the eucalyptus slices are heat-treated at 121℃ for 1 hour, and then re-pulped after cooling. The first stage of pulping uses a 0.5mm grinding disc gap and a solid content of 20%; the second stage of pulping uses a grinding disc gap of 0.15mm and a solid content of 10%.

[0051] Use PFI pulping machine (MarkV1, Hamjern, Norway) for fine grinding, set pressure 3.33N / mm, speed 10000 rpm. Send the refined mechanical pulp to the flat screen (PAPTACC.11P, MessmerSomerville, Germany) for screening, the screen size is 2.5mm, and the screening residue of the three mechanical pulps does not exceed 3%. The screened pulp is filtered with a 200 mesh nylon net, dispersed, and placed in a 50℃ constant temperature ventilated drying oven for use. It was determined that the beating degrees of reed pulp, bamboo pulp and wood pulp were 11.7°SR, 10.5°SR and 12.8°SR, respectively, and the whiteness was 36.75%ISO, 37.02%ISO and 35.10%ISO, respectively.

[0052] Enzyme treatment stage (stage X)

[0053] pH 5.0 and temperature 60℃ were selected as the experimental conditions for enzyme treatment, and the pulp concentration of untreated mechanical pulp was 10%. It should be pointed out that H2O2 cofactor is essential for peroxidase delignification. Although it has the ability to oxidize lignin, the addition amount and reaction temperature do not meet the conditions required for hydrogen peroxide bleaching.

[0054] Chelation treatment (Q stage)

[0055] After X treatment, the pulp concentration is selected as 10% in the chelation treatment stage, 0.5% ethylenediaminetetraacetic acid (EDTA) is added, and the mechanical pulp to be treated with EDTA is placed in a polyethylene sealed bag, kneaded to mix the pulp and the liquid medicine evenly, and placed in a 60°C constant temperature water bath for 60 minutes to remove metal ions in the pulp that may catalyze the decomposition of H2O2. After the chelation is completed, it is cooled to room temperature, and the pulp is washed with deionized water, and finally adjusted to a solid content of 10% for standby use.

[0056] Hydrogen peroxide treatment (P stage)

[0057] The pulp treated in stages X and Q was bleached with H2O2, and the process conditions were 4% H2O2, 2% NaOH, 0.5% MgSO4, 10% pulp concentration, 80°C temperature, and 120 minutes. During the reaction, the pulp was rubbed every 15 minutes to ensure uniform reaction. After bleaching, the pulp was washed with deionized water until neutral, and the moisture was balanced for standby use.

[0058] Copy

[0059] The pulp treated with XQP was placed in a deflaker for 2000 revolutions and was made into sheets using a Kaiser automatic papermaking system (RK3AKWT, Austria RK3A). The basis weight of the paper was 60±1.5 g / m 2 , then placed in a constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) for 24 hours, cut as required, and used to measure strength properties.

[0060] Pulp properties test methods

[0061] Whiteness determination

[0062] The whiteness of the printed sheet was measured using a whiteness meter (CTP-ISO, Technidyne Color Touch, USA). The sample was placed on the test bench for testing and the data was recorded. Each set of conditions was measured 5 times on both the front and back sides and the average value was taken.

[0063] Tensile strength determination

[0064] The tensile index of the paper was measured in a tensile strength instrument (L&WCE062, Lorentzen & Wettre, Sweden). The sample width was 15 mm and the length was 150 mm. The maximum tensile strength, i.e. the maximum tension that the paper can withstand, was measured 3 times for each set of conditions and the average value was taken. The tensile index was calculated by dividing the tensile strength by the paper basis weight.

[0065] Bursting strength determination

[0066] The maximum bursting strength of the paper (bursting index is the ratio of bursting strength to paper basis weight) is measured in a bursting strength tester (L&WCE180, Lorentzen & Wettre, Sweden), that is, the maximum pressure that paper can withstand per unit area. Place the test sample on the top of the instrument diaphragm, press the "Start" button to test, and record the data. Each set of conditions is measured 3 times and the average value is taken.

[0067] Tear strength determination

[0068] The tear strength of the paper was tested in a tear tester (L&W009, Lorentzen & Wettre, Sweden) (the tear index is the ratio of the tear strength to the basis weight of the paper sheet). The paper sample size is 63mm×50mm, fixed on the fixture, press the "CLAMP" key to cut the paper, press the "PEND" key to test, record the data, measure 3 times for each set of conditions, and take the average value.

[0069] Acid soluble lignin and Klason lignin determination

[0070] The acid-soluble lignin and Klason lignin were determined according to the methods of GB / T10337-2008 and GB / T747-2003, respectively.

[0071] Accurately weigh 2g of pulp and extract it with acetone for 6h. After the extraction, air-dry the pulp and react it with 40mL72% sulfuric acid solution at 25℃ for 2h. Then dilute it with water to an acid concentration of 3% and boil it for 4h. Continuously add hot water to make the solution volume constant at 1540mL. After the reaction, wash the residue with distilled water and dry it in an oven at 105℃ to constant weight. The Klason lignin content (%) in eucalyptus pulp is calculated by dividing the mass of the residue after drying by the mass of the absolute dry pulp sample. For bamboo pulp and reed pulp, the residue that has been dried to constant weight needs to be transferred to a high-temperature furnace for burning (900℃) to obtain the ash mass. The Klason lignin content of bamboo pulp and reed pulp (g / g 干浆 ) The mass of the residue after drying minus the mass of the ash after high temperature burning, divided by the mass of the absolute dry pulp sample. The acid soluble lignin was determined by filtering out the supernatant obtained after the acid insoluble lignin was removed. The absorbance of the filtrate at 205nm was measured with a 3% sulfuric acid solution as a control, and the acid soluble lignin content was calculated according to the following formula (g / g 干浆 ). Two parallel groups of each sample were measured at the same time and the average value was taken.

[0072]

[0073] Where A is the absorbance at 205nm; 110 is the absorption coefficient, L·g -1 cm -1 ; m0——the mass of absolute dry pulp, g.

[0074] X-ray Photoelectron Spectroscopy (XPS)

[0075] Accurately weigh 2.0g of pulp with an absolute dry mass, wrap it with pre-extracted filter paper, and extract it with acetone in a Soxhlet extractor for 6 hours to remove the extract. Then wash it with deionized water until it is neutral, flatten it on a glass plate to make a pulp sheet, and air-dry it at room temperature. Use an X-ray photoelectron spectrometer for measurement and analysis. Use the following formula to estimate the content of lignin on the fiber surface.

[0076]

[0077] Among them, O / C 碳水化合物 =0.83, O / C 木质素 =0.33.

[0078] Fiber morphology detection

[0079] Optical microscope observation: After the fibers with different treatment degrees were fully dispersed, the fiber morphology was observed under an optical microscope with a magnification of 100 times.

[0080] The process of fiber analysis is as follows: prepare a fiber suspension with a concentration of 20-35 mg / L, preferably 30 mg / L: weigh 30 mg of sample, stir up and down in a special deagglomerator to disperse the sample, after the sample is evenly dispersed, pour it into a measuring cylinder and add water to 1000 mL, stir evenly. Select the "turntable mode" in the test software for testing. The fiber analyzer calculates the length, diameter, curl content and fine fiber content of about 10,000 fibers.

[0081] Micromorphology analysis

[0082] The pulp fibers were dispersed in deionized water (pulp concentration ≤ 0.2%), and the pulp suspension was dropped onto a mica sheet pre-attached to a metal sheet using a dropper, and dried naturally in a clean environment to avoid dust contamination of the surface. The fiber surface was measured using an atomic force microscope (AFM) (Multimode 8, Bruker, Germany) in the tapping mode.

[0083] Molecular docking of PRLP and lignin model

[0084] Referring to the lignin model database of the Forest Products Laboratory (FPL) of the United States Department of Agriculture, Chem3D was used to draw the 3D models of lignin monomers, dimers, trimers and tetramers (Table 3-2), and AutodockVina was used to perform molecular docking with the PRLP model. The steps for molecular docking and result processing are as follows:

[0085] Obtain the molecular 3D structure of guaiacol from the PubChem database (https: / / pubchem.ncbi.nlm.nih.gov / ), save it in SDF format, open it in Chimera software and save it in PDB format. Open the protein structure PDF file in Autodock software, perform dehydration, hydrogenation and charge balance processing, and output it as a PDBQT file. Output the ligand molecule as a PDBQT file in the Ligand option of Autodock software. Open the protein and ligand molecules in the Grid option and set the box size to The grid length is The box area can completely cover the protein, set the docking parameters in the Docking option, run AutodockVina for molecular docking, and dock 20 times for each set of conditions. After the docking is completed, the best docking conformation is selected to generate a PDB format file, and the results are redrawn and measured using Chimera software, and the amino acid residues that interact with the ligand are analyzed using LigPlus software.

[0086] Examples 1-10

[0087] Examples 1-9 (see Table 1) are different examples using bamboo mechanical pulp.

[0088] Table 1 Summary of various schemes and measurement results of Examples 1-9

[0089]

[0090]

[0091] Note: Raw pulp refers to bamboo mechanical pulp that has not been processed in any way, the same below.

[0092] As can be seen from Table 1, the effect of enzyme dosage on whiteness and burst index is more significant than treatment time and H2O2 addition. Treatment time has a greater impact on tensile index and tear index. For bamboo pulp whiteness, the best solution is the solution in Example 8, with an enzyme dosage of 1.5 g / kg 绝干浆 , the treatment time was 4h, and the amount of H2O2 added was 0.1g / L. After treatment with this scheme, the whiteness of bamboo mechanical pulp increased from 37.02%ISO to 40.65%ISO. Under this condition, compared with the original pulp, the tensile index increased by 15.2%, the burst index increased by 0.9%, and the tear index did not increase. For strength indicators, the burst index and tear index did not change significantly. Both indicators are closely related to the length of the fiber itself, and the use of peroxidase treatment has little effect on the fiber length. Therefore, the enzyme treatment has limited effect on the burst index and tear index of pulp. After enzyme treatment, the tensile index is greatly improved. When the enzyme dosage is 0.5g / kg 绝干浆 , when the treatment time is 4h and the H2O2 addition amount is 0.5g / L, the tensile strength can be increased from 5.38N·m / g to 6.37N·m / g, an increase of 18.4%. Under this condition, the whiteness is increased by 2.58%ISO, the bursting index is increased by 3.4%, and the tearing index is increased by 1.6%. In addition to the fiber length, the tensile index is also related to the fiber bonding strength. After enzyme treatment, the lignin on the fiber surface falls off, exposing the fiber, and more hydrogen bonds can be generated between the fibers, thereby improving the tensile index.

[0093] The inventors calculated the range of the experimental results of each factor level. The range reflects the degree of influence of the factor on the result. The larger the range, the greater the influence of the factor on the experimental result. Combined with the range, it can be seen that the enzyme treatment has the greatest influence on the whiteness index. The theoretically optimal solution is different from the solution of Example 8 above, specifically: enzyme dosage 1.5g / kg 绝干浆 , treatment time 4h, H2O2 addition amount 0.3g / L, the scheme was tested and verified, and the whiteness of the paper made of the treated pulp was 40.70%ISO, the tensile index was 6.39N·m / g, the burst index was 3.27kPa·m2 / g, and the tear index was 0.63mN·m2 / g. Compared with the scheme of Example 8, except for the decrease of burst index

[0094] Except for 0.6%, the other indices are higher than the optimal solution in the experiment. Therefore, this solution is preferred for subsequent bamboo pulp production, i.e., enzyme dosage 1.5 g / kg 绝干浆 , treatment time 4h, H2O2 addition amount 0.3g / L scheme is also used as the technical solution of Example 10 of this application.

[0095] Examples 11-20

[0096] Examples 11-19 are treatment examples of reed mechanical pulp and the corresponding results. See Table 2. From the analysis of the effects of various factors, it can be seen that the enzyme treatment time has the largest range of whiteness, tensile index and tear index results, and the enzyme dosage has the largest range of burst index results. The scheme of Example 8 is adopted, that is, the enzyme dosage is 1.5g / kg 绝干浆 , the treatment time is 4h, and the H2O2 addition amount is 0.1g / L. After treatment, the whiteness of reed pulp can be increased by up to 3.64% ISO. In this scheme, the tensile index of paper is increased by 25.5%, the bursting index is increased by 2.9%, and the tearing index is increased by 3.4%. Enzyme treatment has a great influence on the tensile index of reed mechanical pulp. The enzyme dosage is 0.5g / kg 绝干浆 When the treatment time was 6h and the amount of H2O2 added was 0.3g / L, the tensile index increased by 44.81% at the highest. At the same time, the tear index also increased to a great extent, by 37.9%. The tear index has a lot to do with the contact area between fibers. The larger the contact area, the greater the friction resistance. Therefore, the increase in the tear index means that the enzyme treatment of pulp fibers removes lignin, increases the contact area between fibers, and thus improves its strength performance.

[0097] Table 2 Summary of various schemes and measurement results of Examples 11-19

[0098]

[0099] Through range analysis, the theoretical optimal implementation plan for tensile index is an enzyme dosage of 1.5g / kg绝干浆 , the treatment time was 4h, and the H2O2 addition amount was 0.3g / L. The whiteness was 40.10% ISO, the tensile index was 4.90N·m / g, and the burst index was 3.16kPa·m 2 / g, tear index is 0.68mN·m 2 / g, compared with the preferred solution of Example 8 in Table 2 above, except for the tearing index which is reduced by 15%, the other indices are higher than the optimal solution of Example 8. Therefore, the reed mechanical pulp was subsequently treated with this solution: enzyme dosage 1.5g / kg 绝干浆 , treatment time 6h, H2O2 addition amount 0.3g / L, and this verification scheme is used as the scheme of Example 20 of this application.

[0100] Examples 21-30

[0101] The various embodiments and results of eucalyptus mechanical pulp are listed in Table 3. From this calculation, it can be seen that the whiteness and bursting index of wood pulp are greatly affected by the amount of enzyme, the tensile index is greatly affected by the enzyme treatment time, and the tearing index is greatly affected by the amount of H2O2 added. For the whiteness of wood pulp, the influencing factors are as follows: enzyme dosage > action time > H2O2 addition. Therefore, compared with different embodiments, the better solution is embodiment 3, which is an enzyme dosage of 0.5g / kg 绝干浆 , the treatment time is 6h, and the amount of H2O2 added is 0.3g / L. Under this condition, the whiteness is increased by 7.6%, the ISO tensile index is increased by 8.7%, the burst index is increased by 1.5%, and the tear index is increased by 5.1%. Compared with Yu et al. who used Saccharomonosporaviridis to ferment a Dyp-type peroxidase SviDyP to increase the whiteness of eucalyptus kraft pulp by 3.0% ISO, the naturally extracted peroxidase (PRLP) used in the present invention shows a better and more excellent effect of improving whiteness.

[0102] Table 3 Summary of schemes and results of Examples 21-29

[0103]

[0104] The enzyme treatment time also has a great influence on the tensile index of eucalyptus mechanical pulp. Through the range calculation and deduction, the theoretical optimal scheme for whiteness and tensile index is different from the scheme in Example 3, specifically: enzyme dosage 0.5g / kg absolute dry pulp, treatment time 4h, H2O2 addition 0.3g / L, and enzyme dosage 1.5g / kg absolute dry pulp, treatment time 4h, H2O2 addition 0.3g / L. The two schemes were experimented and verified respectively, and the corresponding whiteness was 40.73% ISO and 40. 61% ISO, tensile index are 23.54N·m / g and 23.99N·m / g respectively, burst index are 3.45kPa·m2 / g and 3.51kPa·m2 / g respectively, tear index are 3.76mN·m2 / g and 3.80mN·m2 / g respectively. After comprehensive analysis, the scheme selected for subsequent experiments is: enzyme treatment conditions are enzyme dosage of 1.5g / kg absolute dry pulp, treatment time of 4h, and H2O2 addition of 0.3g / L is the optimal scheme, which is also used as the scheme of Example 30 of the present application.

[0105] Effect of XQP treatment on lignin content

[0106] On the basis of the above research and work, the best X-stage process conditions were selected, and the acid-soluble lignin and Klason lignin of pulps with different treatment degrees were measured. The results are shown in Table 4. After the three mechanical pulps were treated with peroxidase PRLP (X-stage), the content of both acid-soluble lignin and Klason lignin decreased. The acid-soluble lignin of bamboo pulp, reed pulp and wood pulp decreased by 8.7%, 4.8% and 7.3%, respectively, Klason lignin decreased by 1.6%, 2.3% and 5.5%, respectively, and total lignin decreased by 3.7%, 4.2% and 3.6%, respectively. As mentioned above, peroxidase mainly oxidizes lignin to become free radicals, and the free radicals further react to break the connecting bonds between lignin monomers. These oxidized or partially degraded lignins need subsequent treatment to be separated from the pulp. After XQP treatment, lignin was significantly removed. Compared with the original pulp, the acid-soluble lignin of bamboo pulp, reed pulp and wood pulp decreased by 34.8%, 19.0% and 26.8%, respectively, the Klason lignin decreased by 13.4%, 15.9% and 21.4%, respectively, and the total lignin decreased by 14.8%, 12.5% ​​and 17.9%, respectively. This experiment also used QP segment treatment as a control. Compared with it, X segment pretreatment slightly improved the effect of pulp lignin removal, but it was not very significant. The inventor believes that peroxidase is a large molecule and it is difficult to enter the internal reaction of mechanical pulp fibers. It mainly degrades the lignin on the fiber surface. Its effect requires more precise surface chemical analysis technology to measure.

[0107] Changes in surface lignin content

[0108] After acetone extraction, the pulps in Table 4 were subjected to X-ray photoelectron spectroscopy (XPS) for quantitative analysis of the changes in lignin concentration on the surface of mechanical pulp fibers obtained by different treatment methods. The results are summarized in Figure 1 and Table 4. Pulp full spectrum scan ( Figure 1 ) Only C and O elements showed obvious peaks, and no peaks of other elements were found. According to the different ways in which C atoms are combined with other atoms or atomic groups, the C1s peak of pulp can be divided into four categories: C1, C2, C3 and C4. C1 is a C atom that is only connected to a saturated C atom or a hydrogen atom, or in other words, only C or H is combined with the C atom corresponding to C1, that is, C—C or C—H, and its electron binding energy is about 285eV. All C atoms in cellulose and hemicellulose molecules are connected to at least one O atom, so there are no C1-type C atoms. Therefore, C1 mainly comes from lignin and extracts in pulp. For raw materials after extraction, C1 can be considered to come from lignin. C2 is a C atom connected to one non-carbonyl O atom, that is, C—O in alcohol and phenol. Both cellulose and hemicellulose in pulp contain a large number of hydroxyl groups connected to C atoms, and the electronegativity of hydroxyl groups is large, so the electron binding energy of C2 increases to about 286.5eV. C3 is a C atom connected to one carbonyl O atom or two non-carbonyl O atoms, that is, C=O or O-C-O structure. C3 mainly comes from the acetal structure in hemicellulose and the carbonyl in lignin, and the electron binding energy is about 288eV. C4 is a C atom connected to one carbonyl O atom and one non-carbonyl O atom, that is, O-C=O structure, mostly from the acetyl group of hemicellulose and the fatty acid in the extract, and the electron binding energy is about 289eV.

[0109] Table 4 Effects of several treatment methods on pulp lignin content

[0110]

[0111]

[0112] Figure 1The C1s peak diagram of several mechanical pulps was calibrated with the standard binding energy of C1s being 285 eV. Combined with Table 4, it can be seen that after PRLP peroxidase treatment, the C1 content of bamboo pulp, reed pulp and wood pulp decreased by 3.1%, 1.9% and 11.4%, respectively, indicating that the content of lignin on the surface of pulp decreased. The C3 content of bamboo pulp, reed pulp and wood pulp increased by 8.8%, 11.41% and 3.8%, respectively. It may be that the lignin rich on the surface of mechanical pulp was oxidized on the surface of pulp as a substrate of peroxidase. The content of C2 and C4 in bamboo pulp was almost unchanged, indicating that the product of PRLP oxidation of bamboo pulp lignin failed to dissolve and separate. The content of C2 in reed pulp and wood pulp increased by 3.1% and 12.7%, respectively, indicating that PRLP achieved oxidation removal of part of the lignin on the surface of reed pulp and wood pulp fibers, exposing more brown cellulose. The C4 content of reed pulp and wood pulp decreased by 61.3% and increased by 51.9%, respectively, corresponding to the removal of acetyl structures in hemicellulose by PRLP. Compared with the original pulp of each pulp, the C1 content of bamboo pulp, reed pulp and wood pulp decreased by 16.8%, 20.4% and 39.4%, respectively, and the C2 content increased by 15.8%, 17.7% and 37.3%, respectively, after XQP treatment. This is because the H2O2 bleaching treatment removed a large amount of lignin on the surface of the pulp, exposing the cellulose. The C1 content of bamboo pulp, reed pulp and wood pulp treated with QP was 2.8%, 1.5% and 5.9% higher than that of XQP treatment, and the C2 content was 0.5%, 0.5% and 6.3% lower than that of XQP treatment, respectively. This shows that PRLP plays a certain role in assisting delignification in the H2O2 bleaching process, especially for eucalyptus mechanical pulp. In addition, the oxygen-to-carbon ratio (O / C) can reflect the surface lignin content of pulp. The higher the O / C, the higher the carbohydrate content on the fiber surface, and the lower the O / C, the higher the lignin content on the fiber surface.

[0113] The calculation results listed in Table 5 show that the O / C of bamboo mechanical pulp after X-stage treatment increased by 1.36% compared with the original pulp, and the surface lignin concentration decreased by 2.72%. The surface lignin concentrations of bamboo mechanical pulp treated with XQP and QP were 53.80% and 59.08%, respectively, which were 25.72% and 20.44% lower than the original pulp. After X-stage treatment, the O / C of reed mechanical pulp increased by 1.61% compared with the original pulp, and the surface lignin concentration decreased by 3.22%; the O / C of reed mechanical pulp treated with XQP increased by 4.05% compared with that treated with QP, and the surface lignin concentration decreased by 7.96%. The O / C of eucalyptus mechanical pulp after X-stage treatment increased by 1.24%, and the surface lignin concentration decreased by 2.48%. After XQP stage treatment, the O / C increased by 18.40% compared with the original pulp, and the surface lignin content decreased by 36.8%, which was 6.42% lower than that of the surface lignin content treated with QP. The above data show that PRLP peroxidase removes lignin from the surface of pulp fibers and also has a significant auxiliary gain effect on the subsequent H2O2 bleaching to remove lignin.

[0114] Table 5 Summary of O / C and surface lignin concentration of different pulps

[0115]

[0116] Effects of XQP Treatment on Mechanical Pulp Properties and Fiber Morphology

[0117] The results of pulp whiteness and mechanical strength performance tests are shown in Table 6. Compared with the original pulp, after the peroxidase X-stage treatment, the whiteness of bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp increased by 3.68% ISO, 3.35% ISO and 5.51% ISO respectively; the whiteness of XQP bamboo pulp, reed pulp and wood pulp increased by 3.34% ISO, 3.78% ISO and 2.12% ISO respectively compared with their respective QP control samples. Therefore, it can be determined that the natural peroxidase pretreatment used in the present application improves the bleachability of mechanical pulp and is conducive to the increase of the whiteness of mechanical pulp. The tensile index of XQP bamboo pulp, reed pulp and wood pulp reached 8.57N·m / g, 5.60N·m / g and 25.69N·m / g, respectively, which was 5.7%, 3.1% and 6.3% higher than that of QP, and 50.7%, 61.1% and 22.3% higher than that of original pulp. The tensile index reflects the bonding force between fibers, which is related to the interweaving arrangement of fibers and the strength of the fibers themselves. XQP treatment removes part of the lignin on the surface of mechanical pulp (Table 6), exposing more fibers and increasing the bonding force between fibers. The tear index of bamboo pulp, reed pulp and wood pulp after XQP treatment increased by 53.2%, 36.2% and 11.0% respectively compared with original pulp, and the burst index increased by 2.4%, 10.2% and 7.3%. The tear index of pulp is closely related to the fiber length and surface roughness. After XQP treatment, the fiber length has not increased, but combined with the microscope image, the fiber surface has filaments and hairiness, which increases the roughness, so the tear index of mechanical pulp has increased. The tear resistance index is affected by the bonding force and average length between fibers. As delignification proceeds, the fiber cell wall is destroyed, exposing fine fibers, which increases the bonding force between fibers.

[0118] Table 6 Summary of the test results of XQP treatment on mechanical pulp properties

[0119]

[0120]

[0121] Fiber morphology analysis

[0122] The fiber length, width, curl content and fine fiber content of various pulps were measured. The results are shown in Table 7.

[0123] After the X-stage enzyme treatment, the fiber length did not differ much, probably because the fine fibers had a large specific surface area and were easily bonded by the oxidative cross-linking of the enzyme, so their content decreased slightly, but the effect on the size and number of long fibers was not obvious. After XQP treatment, the fiber lengths of bamboo, reed and eucalyptus mechanical pulps decreased by 9.2%, 7.6% and 6.7%, respectively, but compared with the morphology of QP-treated fibers, the fiber lengths still increased slightly, by 0.7%, 1.6% and 0.5%, respectively. H2O2 bleaching adds a strong alkaline chemical NaOH, which causes the fibers to swell and break, resulting in a decrease in fiber length and an increase in the content of fine fibers. The fiber morphology of the mechanical pulp treated with XQP was not much different from that of the QP control group, indicating that the effect of palm peroxidase on fiber morphology was not significant.

[0124] Table 7 Summary of the effects of XQP treatment on mechanical pulp fiber morphology

[0125]

[0126]

[0127] Note: The fiber length in Table 7 is the double weight average fiber length.

[0128] Optical microscope photos of various pulp fibers are summarized in Figure 2 In the figure, it can be observed that after the X-stage enzyme treatment, the fibers of the three pulps all had slight fibrillation and fluffing, indicating that the peroxidase was also damaged to a certain extent while delignifying. After the XQP treatment, the fiber lengths of the three types did not change significantly, the fibers had fibrillation and brooming, and the fiber width increased. It can be clearly seen that fine fibers were separated from the ends of the fibers, and the content of fine fibers in the wood pulp increased, which shows that the XQP treatment caused swelling and damage to the fibers, but the overall morphology of the three pulp fibers did not change significantly, and the fiber integrity was good. The fiber morphology of the XQP treatment was similar to that of the QP treatment alone, which was consistent with the data measured by the fiber analyzer.

[0129] The surface morphology of bamboo pulp, reed pulp and eucalyptus mechanical pulp fibers before and after XQP treatment was measured by tapping AFM. Figure 3 As shown, Figure 3The bright raised particles in the middle are typical characteristics of amorphous and hydrophobic lignin, and the dark and striped oriented parts are consistent with the characteristics of hydrophilic cellulose microfibrils and macrofibrils. The surface of the original pulp fiber is rough and covered with a large number of hydrophobic particles. After XQP treatment, the three-dimensional morphology of the fiber surface becomes smoother and highly uniform. This is because peroxidase and H2O2 bleaching remove part of the lignin on the fiber surface and expose the fiber. In particular, the surface of XQP eucalyptus mechanical pulp is smooth and the microfibrils are clearly defined, which is consistent with the XPS result that XQP eucalyptus mechanical pulp removes 37% of the surface lignin.

[0130] Molecular docking of PRLP and lignin model compound

[0131] XPS analysis proved that PRLP can catalyze the reaction of bamboo, reed and eucalyptus lignin. Their lignin is a natural polymer composed of p-coumaryl alcohol (PA), coniferyl alcohol (CA) and sinapyl alcohol (SA). They need to be oxidized, and some structural groups enter or at least approach the peroxide active area. The size and structure of these structural groups determine their binding energy at the effective site. Therefore, molecular docking can confirm XPS data and help understand the interaction between PRLP and lignin. The docking results of 12 lignin models with PRLP are listed in Table 8. The number of methoxyl groups in the three raw materials, namely PA, CA and SA, increases successively, and the binding energy (absolute value) of docking with PRLP also increases successively. These monomers can enter the active pocket of PRLP. All three monomers form hydrogen bonds with Arg70, Glu100, Ser105 and Arg207. The amino acid residues that bind to these monomers by hydrophobic force are Gln101, Ile1701, Pro171, Thr172, Pro173, Asn210 and the heme group. Models 4-8 are dimers, involving β-O-4, β-1, β-5, β-β, 5-5 and other connection forms. The higher binding energy shows that these different connection forms can enter the active area of ​​PRLP and bind. 9-12 are trimers, tetramers and pentamers. Because their three-dimensional size is larger than that of monomers and dimers, they bind to the edge of the catalytic pocket. The absolute value of the binding energy generally decreases with the increase of molecular volume ( Figure 4 ), but the binding energy of the pentamer is still -4.7kcal / mol, which indicates that the pentamer of lignin can stably bind to the catalytic region of PRLP, thereby generating an anti-oxidation reaction. Liu Hao et al. studied the molecular docking of laccase with lignin model substances. The docking binding energy of lignin tetramer with laccase is only -0.06kcal / mol, which is extremely unstable and cannot be effectively bound in the active region.

[0132] Table 8 Molecular docking results of PRLP and lignin model

[0133]

[0134]

[0135] The above are the specific experimental methods and preferred implementations of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for treating mechanical pulp with a biological enzyme extracted from pure plants, characterized in that: The processing method is completed according to any of the following processing procedures: Treatment process (A): Use natural peroxidase to treat mechanical pulp at pH 5.0 and temperature 60°C for 2-6 hours. The amount of peroxidase added is 0.5-1.5 g / kg. 绝干浆 The reaction concentration of the mechanical pulp is 10%, and the mechanical pulp is washed with deionized water to balance the moisture and complete the treatment; Treatment process (B): First, the mechanical pulp is treated with naturally extracted peroxidase at pH 5.0 and 60°C for 2-6 hours. The amount of peroxidase added is 0.5-1.5 g / kg. 绝干浆 The reaction concentration of the mechanical pulp is 10%, and the mechanical pulp is washed with deionized water to adjust the solid content of the mechanical pulp to 10% for standby use; 5g / L ethylenediaminetetraacetic acid is added to the mechanical pulp treated with peroxidase, and the mechanical pulp to be treated with ethylenediaminetetraacetic acid is placed in a polyethylene sealed bag, kneaded to mix the mechanical pulp and the liquid medicine evenly, and placed in a 60°C constant temperature water bath for 60 minutes. After the end, it is cooled to room temperature, and the mechanical pulp is washed with deionized water to adjust the solid content to 10%; the mechanical pulp treated with ethylenediaminetetraacetic acid is bleached with H2O2, and the process conditions are H2O2 addition 40g / L, NaOH 20g / L, MgSO4 5g / L, mechanical pulp concentration 10%, and reaction at a temperature of 80°C for 120min; during the reaction process, knead once every 15min to ensure uniform reaction. After bleaching, wash with deionized water to neutrality, balance the moisture, and the treatment is completed.

2. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1, characterized in that: The peroxidase is extracted from the leaves of Eryngium serrata, and the enzyme activity of the peroxidase is 35.64±4.77 U / mL.

3. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1, characterized in that: When the mechanical pulp is bamboo mechanical pulp, the amount of peroxidase used in the peroxidase treatment process is 1.5 g / kg 绝干浆 , treatment time 4h, H2O2 addition amount in H2O2 bleaching process 0.3g / L; when mechanical pulp is reed mechanical pulp, the enzyme dosage of peroxidase in peroxidase treatment process is 1.5g / kg 绝干浆 , treatment time 6h, H2O2 addition amount in H2O2 bleaching process 0.3g / L; when mechanical pulp is eucalyptus mechanical pulp, the enzyme dosage of peroxidase in peroxidase treatment process is 1.5g / kg 绝干浆 , treatment time is 4h, and the amount of H2O2 added during H2O2 bleaching is 0.3g / L.

4. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1 or 3, characterized in that: When the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the acid-soluble lignin of the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated according to treatment process (B) decreases by 34.8%, 19.0%, and 26.8%, respectively, and / or the Klason lignin decreases by 13.4%, 15.9%, and 21.4%, respectively, and / or the total lignin decreases by 14.8%, 12.5%, and 17.9%, respectively.

5. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1 or 3, characterized in that: When the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the acid-soluble lignin of the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated according to process (A) is reduced by 8.7%, 4.8%, and 7.3%, respectively, and / or the Klason lignin is reduced by 1.6%, 2.3%, and 5.5%, respectively, and / or the total lignin is reduced by 3.7%, 4.2%, and 3.6%, respectively.

6. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1 or 3, characterized in that: When the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the content of C atoms connected only to saturated C atoms or hydrogen atoms in the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated by treatment process (A) is reduced by 3.1%, 1.9%, and 11.4%, respectively, and the content of C atoms connected to one carbonyl O atom or two non-carbonyl O atoms is increased by 8.8%, 11.41%, and 3.8%, respectively.

7. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1 or 3, characterized in that: When the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the contents of C atoms connected only to saturated C atoms or hydrogen atoms in the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated by treatment process (B) are reduced by 16.8%, 20.4%, and 39.4%, respectively, and the contents of C atoms connected to one non-carbonyl O atom are increased by 15.8%, 17.7%, and 37.3%, respectively.

8. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1 or 3, characterized in that: Specifically include: When the mechanical pulp is reed mechanical pulp, after being treated by process (A), the O / C is increased by 1.61% compared with the original pulp; after being treated by stage X, the O / C of the reed mechanical pulp is increased by 1.61% compared with the original pulp, and the surface lignin concentration is reduced by 3.22%; when the mechanical pulp is bamboo mechanical pulp, after being treated by process (A), the O / C of the bamboo mechanical pulp is increased by 1.36% compared with the original pulp, and the surface lignin concentration is reduced by 2.72%; when the mechanical pulp is eucalyptus mechanical pulp, after being treated by process (A), the O / C of the eucalyptus mechanical pulp is increased by 1.24%, and the surface lignin concentration is reduced by 2.48%.

9. The method for treating mechanical pulp with biological enzymes extracted from pure plants according to claim 1 or 3, characterized in that: When the mechanical pulp is bamboo mechanical pulp, reed mechanical pulp, or eucalyptus mechanical pulp, the fiber lengths of the bamboo mechanical pulp, reed mechanical pulp, and eucalyptus mechanical pulp treated by the treatment process (B) are reduced by 9.2%, 7.6%, and 6.7%, respectively.

10. A paper product prepared from mechanical pulp treated by the method for treating mechanical pulp with a biological enzyme extracted from pure plants as claimed in any one of claims 1 to 9, characterized in that: The paper product satisfies at least one of the following conditions (1) to (5): (1) The whiteness of the bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp paper products obtained by the treatment process (A) are 40.70% ISO, 40.1% ISO and 40.61% ISO respectively; (2) The paper products made of bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by treatment process (A) have whiteness increased by 3.68% ISO, 3.35% ISO and 5.51% ISO respectively compared with the paper products made of the original pulp; (3) The paper products prepared from the bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by the treatment process (B) have tensile indices of 8.57 N·m / g, 5.60 N·m / g and 25.69 N·m / g, respectively; (4) The tensile index of the paper products prepared from the bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by the treatment process (B) is increased by 50.7%, 61.1% and 22.3% respectively compared with the tensile index of the original pulp; (5) The tearing index of paper products made from bamboo mechanical pulp, reed mechanical pulp and eucalyptus mechanical pulp obtained by treatment process (B) was increased by 53.2%, 36.2% and 11.0% compared with the paper products made from original pulp, and the bursting index was increased by 2.4%, 10.2% and 7.3%, respectively.

Citation Information

Patent Citations

  • Bleaching of pulp

    CN103080415A

  • Method for all chlorine free bleaching paper pulp by biological technology

    CN1296099A

  • Non-chlorine bleaching of kraft pulp

    US5691193A